Characteristics of natural fiber composites materials reinforced with aluminum and copper powder for the performance of automatic motorcycle clutch pad - Riyadi, Ahmad; Kholil, Ahmad; Siregar, Januar Parlaungan; Dwiyati, Siska Titik; Pratama, Danang Budi; Setiawan, Ari; Syaefuddin, Eko Arif (Universitas Muhammadiyah Magelang, 2023)
This article presents a comprehensive investigation into the characteristics of natural fiber composite (NFC) materials reinforced with aluminum and copper powder for performance automatic motorcycle clutch pads. With a focus on environmentally friendly and high-performance materials, this study explores the effects of incorporating aluminum and copper powders into natural fiber composites on key properties such as friction, wear resistance, hardness, oil absorption, and microstructural features for performance clutch pads. The friction characteristic of the composites was evaluated using a pin-on-disc tribometer, while wear resistance was assessed through pin-on-disc wear tests. Hardness properties were determined using standardized methods, and oil absorption behavior was examined by immersing the composites in lubricating oil. Additionally, scanning electron microscopy (SEM) was utilized to study the microstructure of the composites. The performance of the clutch pad sample was tested with an automatic motorcycle by a chassis dyno test. The results revealed that the inclusion of aluminum and copper powders significantly improved frictional characteristics, wear resistance, hardness, and oil absorption capacity of the composites. SEM images displayed effective bonding between the reinforcement particles and the composite matrix. Samples 3-5 have a performance increase of 4.8% at lower rpm than a genuine clutch. The advantages of both low and high speed remain smooth in transmitting power to the wheel. These findings suggest that the developed natural fiber composites show promising potential for enhancing the performance and durability of automatic motorcycle clutch pads, making them attractive alternatives to conventional materials in automotive applications.